1999
DOI: 10.1021/jm980733i
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Calcium Mobilizing, and Physicochemical Properties of d-chiro-Inositol 1,3,4,6-Tetrakisphosphate, a Novel and Potent Ligand at the d-myo-Inositol 1,4,5-Trisphosphate Receptor

Abstract: The synthesis of a novel and potent ligand at the D-myo-inositol 1,4, 5-trisphosphate receptor (InsP3R) is described. D-chiro-Inositol 1,3, 4,6-tetrakisphosphate (7) and L-chiro-inositol 1,3,4, 6-tetrakisphosphate (ent-7) have been synthesized from D-2, 5-di-O-benzyl-chiro-inositol and L-2,5-di-O-benzyl-chiro-inositol, respectively. The potency of binding and Ca2+ release of 7 and ent-7 were examined in L15 and Lvec cells. 7 was a full agonist at the InsP3R in both cells, and ent-7 was inactive. The results ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 42 publications
0
17
1
4
Order By: Relevance
“…d-chiro-Inositol-1,3,4,6-tetrakisphosphate (107;F igure 5) has been synthesized from d-pinitol (the 3-O-methyl derivative of d-chiro-inositol) via the 2,5-di-O-benzyl-protected intermediate then phosphorylation of the hydroxy groups followed by deprotection. [83] Starting from d-pinitol and proceeding via the 1,6-di-O-benzyl-protected intermediate, the synthesis of d-chiro-inositol 2,3,4,5-tetrakisphosphate (108;F igure 5) has also been described via the intermediate [84] and d-chiro-inositol-1,3,4-trisphosphate (109)h as been synthesized from d-1,2,5- [85] Thesyntheses of fagopyritols A1 and B1 (galactopyranosyl derivatives of d-chiro-inositol), the biological role of which are discussed in the Supporting Information (SI_2), have been described. [86] Starting from the appropriate penta-O-benzyl-d-chiro-inositol, all six isomeric d-galactosaminopyranosyl-d-chiro-inositols have been prepared.…”
Section: Overview Of D-chiro-inositol Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…d-chiro-Inositol-1,3,4,6-tetrakisphosphate (107;F igure 5) has been synthesized from d-pinitol (the 3-O-methyl derivative of d-chiro-inositol) via the 2,5-di-O-benzyl-protected intermediate then phosphorylation of the hydroxy groups followed by deprotection. [83] Starting from d-pinitol and proceeding via the 1,6-di-O-benzyl-protected intermediate, the synthesis of d-chiro-inositol 2,3,4,5-tetrakisphosphate (108;F igure 5) has also been described via the intermediate [84] and d-chiro-inositol-1,3,4-trisphosphate (109)h as been synthesized from d-1,2,5- [85] Thesyntheses of fagopyritols A1 and B1 (galactopyranosyl derivatives of d-chiro-inositol), the biological role of which are discussed in the Supporting Information (SI_2), have been described. [86] Starting from the appropriate penta-O-benzyl-d-chiro-inositol, all six isomeric d-galactosaminopyranosyl-d-chiro-inositols have been prepared.…”
Section: Overview Of D-chiro-inositol Derivativesmentioning
confidence: 99%
“…[146] Chemically synthesized GPIs containing d-chiro-inositol are cleaved by GPI-specific phospholipase Db ut not by phosphatidylinositol-specific phospholipase C. [147] d-chiro-Inositol 1,3,4,6-tetrakisphosphate (107)i safull agonist of the inositol trisphosphate receptor in two cell lines, but the enantiomer is inactive. [83] With an IC 50 value of 1.5 mm, d-chiro-inositol 2,3,4,5-tetrakisphosphate (108)i sapotent inhibitor of Ins(3,4,5,6)P 4 1-kinase/Ins(1,3,4)P 3 5/6 kinase but its enantiomer is more than 20-fold less active. [84] Therelease of calcium from saponin-permeabilizedr at basophilic leukaemia cells is inhibited by d-chiro-inositol 1,3,4-trisphosphate (109)w ith EC 50 = 4.2 mm,w hile the enantiomer has EC 50 = 120 mm.…”
Section: D-chiro-inositol Phosphatesmentioning
confidence: 99%
“…There is evidence, however, that (1L) chiro ‐phosphatidylinositol is a substrate for phosphatidylinositol‐specific phospholipase C, whereas (1D) chiro ‐phospha‐tidylinositol is not (Bruzik et al 1994). Synthetic non‐ myo ‐po‐lyphosphoinositols have been shown to displace myo ‐inositol trisphosphate from its receptor and mobilize the release of calcium (Lampe and Potter et al 1993; Liu et al 1999; Liu et al 2001; Tegge et al 1991). Though scyllo ‐inositol was not found to be an endogenous component of the phosphoinositide fraction in this study, previous results from this laboratory have shown that Tetrahymena presented with radiolabeled scyllo ‐ino‐sitol incorporate it, intact, into the inositol‐containing lipid fraction (Ryals and Kersting 1999).…”
Section: Resultsmentioning
confidence: 99%
“…[146] Chemically synthesized GPIs containing D-chiro-inositol are cleaved by GPI-specific phospholipase D but not by phosphatidylinositol-specific phospholipase C. [147] D-chiro-Inositol 1,3,4,6-tetrakisphosphate (107) is a full agonist of the inositol trisphosphate receptor in two cell lines, but the enantiomer is inactive. [83] With an IC 50 of 1.5μM D-chiroinositol 2,3,4,5-tetrakisphosphate (108) is a potent inhibitor of Ins(3,4,5,6)P 4 1-kinase/ Ins(1,3,4)P 3 5/6 kinase but its enantiomer is more than 20-fold less active. [84] The release of calcium from saponin-permeabilized rat basophilic leukaemia cells is inhibited by D-chiroinositol 1,3,4-trisphosphate (109) with EC 50 = 4.2μM while the enantiomer has EC 50 = 120μM.…”
Section: D-chiro-inositol Phosphatesmentioning
confidence: 99%
“…L-chiro-Inositol-1,3,4,6-tetrakisphosphate (121, in Figure 8), [83] L-chiro-inositol-2,3,4,5-tetrakisphosphate (122) [84] and L-chiro-inositol-1,3,4-trisphosphate (123), [85] when compared with their D-chiro-inositol equivalents, are less potent inhibitors/agonists of the inositol trisphosphate receptor, Ins(3,4,5,6)P 4 1-kinase/Ins(1,3,4)P 3 5/6 kinase, and the release of calcium from saponin-permeabilized rat basophilic leukaemia (RBL) cells, respectively. The synthesis of L-chiro-Ins(1,2,3,4,5,6)P 6 and its subsequent degradation to other L-chiro-inositol phosphates by phytases has been described.…”
Section: L-chiro-inositol Phosphatesmentioning
confidence: 99%